An overview of Brazilian companies' readiness to implement industrial symbiosis - Agudo, Fabiana Liar [UNESP]; Bezerra, Bárbara Stolte [UNESP]; Gobbo Júnior, José Alcides [UNESP] (Wiley, 2024)
Industrial symbiosis (IS) is a strategy that focuses on the exchange of resources between colocated industries. Despite the benefits of IS, companies often face challenges in implementing it, primarily due to technical, economic, and information barriers. Therefore, this paper aims to investigate the feasibility of implementing IS among Brazilian companies. To achieve this, a survey was conducted with 201 colocated companies using a previously developed instrument to assess their levels of symbiotic readiness. The findings resulted in the creation of a typology of symbiotic readiness levels, accompanied by practical recommendations for each level. In general, the surveyed companies are making progress toward implementing IS, as evidenced by their attempts to exchange waste and by-products with other colocated industries. However, overcoming barriers related to information sharing, trust-building, access conditions, infrastructure, and partnership formation remains challenging. This study provides valuable evidence from an emerging country regarding the readiness levels of companies to implement IS, offering insights and recommendations for managers and public authorities to promote IS. It is important to note that as companies reach mature stages of IS implementation, they can collaborate to transform the conditions of the industrial parks, ultimately fostering future industrial ecosystems.
Keywords: assessment instrument; business efficiency; circularity; industrial park; resource management